Implementation Of The Pediatric Early Warning System In Children With Chronic Diseases: Systematic Review - Meidiana Bangun; Nani Nurhaeni; Allendekania Allendekania (Malahayati Nursing Journal, 2022)
ABSTRACT  Pediatric early warning system (PEWS) can be an early detection of worsening in pediatric patients with chronic diseases, quantitative studies related to the implementation of PEWS in children with chronic diseases have been carried out in various countries including the USA, Guatemala and China. The purpose of this review is to determine the implementation of PEWS in children with chronic diseases. This literature study uses a review method approach, data sources through Proquest, Science Key, Pubmed, JStore and CHINIL. Search articles using Indonesian and English keywords. Inclusion criteria and articles analyzed: research on the topic of PEWS in children with cancer. Articles obtained A total of 1,260 journals were taken. However, only 22 journals met the criteria for the last 10 years. In the end, only 6 journals that met the inclusion criteria were analyzed. The results of the analysis show that PEWS is also suitable for use in low-income countries, or in developing countries. The currently developed PEWS is in accordance with the criteria for pediatric patients treated in hemato-oncology wards, and can reduce hospital costs in the country in addition to optimizing existing resource. Keywords: Implementation, Pediatric Early Warning System, Children With  Cancer, Chronic Disease